Keyphrase Extraction from Scientific Articles - Navitha Abhinaya S,; Neha H,; Papireddigari Renusree,; Sowmya Lakshmi B. S, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Keyphrase extraction is a crucial task in natural language processing (NLP) that involves identifying important terms and phrases in a text. This paper presents a methodology for extracting keyphrases from scientific articles using a combination of preprocessing techniques and the term frequency-inverse document frequency (TF-IDF) algorithm. The approach includes tokenization, stopword removal, and punctuation elimination, followed by the application of the TF-IDF vectorizer to identify and score keyphrases. The results demonstrate the effectiveness of the method in highlighting significant terms in scientific texts.
Keywords: Keyphrase Extraction; Natural Language Processing; TF-IDF; Scientific Articles; Text Preprocessing